The Leukotriene Receptor Antagonist Montelukast as a Potential COVID-19 Therapeutic - Aigner, Ludwig; Pietrantonio, Frank; Bessa de Sousa, Diana Marisa; Michael, Johanna; Schuster, Daniela; Reitsamer, Herbert Anton; Zerbe, Horst; Studnicka, Michael (Frontiers in Molecular Biosciences, 2020)
The emergence and global impact of COVID-19 has focused the scientific and medical community on the pivotal influential role of respiratory viruses as causes of severe pneumonia, on the understanding of the underlying pathomechanisms, and on potential treatment for COVID-19. The latter concentrates on four different strategies: i) antiviral treatments to limit the entry of the virus into the cell and its propagation, ii) anti-inflammatory treatment to reduce the impact of COVID-19 associated inflammation and cytokine storm, iii) treatment using cardiovascular medication to reduce COVID-19 associated thrombosis and vascular damage, and iv) treatment to reduce the COVID-19 associated lung injury. Ideally, effective COVID-19 treatment should target as many of these mechanisms as possible arguing for the search of common denominators as potential drug targets. Leukotrienes and their receptors qualify as such targets: they are lipid mediators of inflammation and tissue damage and well-established targets in respiratory diseases like asthma. Besides their role in inflammation, they are involved in various other aspects of lung pathologies like vascular damage, thrombosis, and fibrotic response, in brain and retinal damages, and in cardiovascular disease. In consequence, leukotriene receptor antagonists might be potential candidates for COVID-19 therapeutics. This review summarizes the current knowledge on the potential involvement of leukotrienes in COVID-19, and the rational for the use of the leukotriene receptor antagonist montelukast as a COVID-19 therapeutic.